Pengaruh Bauran Pemasaran Terhadap Keputusan Nasabah Menggunakan Produk Jasa Keuangan Syariah Perspektif Islamic Marketing Ethics - muhammad suhaidi (Jurnal Ilmiah Ekonomi Islam, 2022)
Islamic marketing ethics (Islamic marketing ethics) is a marketing activity that is based on the spirit of worshiping Allah SWT and optimally trying to improve the welfare of the community, not for the interests of groups let alone personal interests and carrying out marketing functions in an Islamic way. An effective marketing program integrates all elements of the marketing mix into a marketing program designed to achieve the company's marketing objectives by delivering value to customers. The formulation of the problem in this study is whether Islamic marketing ethics in the analysis of the marketing mix in the context of product, price, distribution and promotion has a significant effect on customer decisions to use Islamic financial services at BMT Assyafi'iyah Karang Anyar, South Lampung. Based on the analysis in this study, it is known that the independent variables in Islamic marketing ethics in the analysis of the marketing mix, namely Product (X1), Price (X2), Distribution (X3) and Promotion (X4) have a simultaneous effect on the dependent variable, namely Customer Decision (Y). ). This can be seen from the results of the comparison of the value of Fcount > Ftable of 16,644 > 2.48. Partially there is only one variable that affects customer decisions, namely the price variable (X2) with a tcount of 7.872, while the product variables (X1), distribution (X3), and promotions (X4) do not partially affect the customer's decision to use financial service products. sharia in BMT Asyafi'iyah. In general, Islamic marketing ethics in the context of products, prices, distributions and promotions carried out by BMT Asyafi'iyah Karang Anyar are good and in accordance with sharia principles, this can be seen from the distribution of the majority of respondents' answers who chose to agree on each indicator of Islamic marketing ethics. product context, pricing, distribution and promotion.